Residence-based disparities of composite index of anthropometric failures in East African under five children; multivariate decomposition analysis - Aznamariam Ayres; Yawkal Tsega; Abel Endawkie; Shimels Derso Kebede; Eyob Tilahun Abeje; Ermias Bekele Enyew; Chala Daba; Lakew Asmare; Amare Muche; Fekade Demeke Bayou; Mastewal Arefaynie; Asnakew Molla Mekonen; et al. (BMC Public Health)
Abstract Background Undernutrition remains a global challenge and public health concern, despite the presence of policies, programs and interventions. There is substantial evidence that the majority of the rural children under-5 years old have composite index of anthropometric failure than the urban counter parts. Hence, identifying the main contributors of these disparities will help health policy makers, program designers and implementers for the reduction of composite index of anthropometric failures in children under-5 years old in the study areas. Methods The most recent and nationally representative samples of demographic and health surveys of five East African countries data were used for the current study. To appreciate the residence-based differences of composite index of anthropometric failure in under-5 children, the Blinder-Oaxaca decomposition analysis and its extensions were employed to determine the effects of covariates and coefficients. The country specific survey data analysis was performed. Results The current study revealed that the burden of composite index of anthropometric failure (CIAF) in under-5 children were 40.69%, 22.04%, 34.06%, 31.99%, and 33.27% in Ethiopia, Kenya, Rwanda, Uganda, and Tanzania respectively. The residence-based differences in CIAF were 25.49%, 11.38%, 27%, 22.15%, and 20.55% in Ethiopia, Kenya, Rwanda, Uganda, and Tanzania respectively. Results of the Blinder-Oaxaca decomposition analysis and its extensions revealed that 100% of the rural–urban children under-5 composite index of anthropometric failure disparity was explained by endowment characteristics (covariate effect). Wealth index, mother’s education, age of child, type of birth, sex of child and birth interval inequality between rural and urban households explains most of the composite index of anthropometric failure disparity in children under-5 years old. Conclusions The residence-based CIAF differences were high in all study countries. The rural–urban CIAF gap is ascribed by household, maternal and child characteristics. This result implies that rural children under-5 is disproportionally disadvantaged with respect to characteristics than their consequences. Through identification of the underlying factors behind the rural–urban CIAF disparities, the result of this study is important in planning effective intervention measures aiming at reducing residence-based inequalities and the population health outcomes. Therefore, should be given for rural children to reduce CIAF by improving house hold wealth index, women education and attentions to older children, and female children.